WASILAH DAKWAH: ANALISIS KONSEP DALAM PERSPEKTIF ONTOLOGI - Surizkika , Aldi (JURNAL SAHID DA'WATII, 2024)
This study aims to analyze the concept of wasilah da'wah in an ontological structure with special emphasis on the theoretical framework of Islamic turās. Wasilah da'wah, also known as media or means, plays an important role in improving the efficiency of da'wah activists in carrying out their duties. However, a lack of understanding of the nature of wasilah da'wah is one of the factors causing the lack of effectiveness and efficiency in da'wah. Previous research has focused more on the epistemology and axiology aspects of waṣīlah al-da'wah, but not much on the basic concept (ontology) in the conceptual framework of Islamic turās. This research uses a qualitative approach with content analysis as its research design. Data and findings were obtained from primary sources collected through document analysis from relevant literature books, journals, theses, dissertations, conference papers, and magazines. Thematic analysis was used to identify, analyze, and interpret patterns in qualitative data. The results of this study reveal that wasilah da'wah is a means that brings people closer to the purpose of da'wah. In the current era of the information and communication revolution, the use of modern media provides great opportunities for preachers to spread the message of Islam effectively. In their duty as messengers of Allah, preachers must utilize these technological advances wisely. This research provides a deeper theoretical understanding of the concept of wasilah da'wah within the framework of Islamic turās. It is hoped that this research can contribute to improving the effectiveness and efficiency of da'wah, as well as enriching the discourse of da'wah science related to the concept of wasilah.